UHPLC-MS/MS determination of varietal thiol precursors in Sauvignon Blanc grapes - Andreja Vanzo (Nature Portfolio, 2017)
Abstract Varietal thiol precursors in grapes are subject to metabolic changes during post-harvest treatments. Metabolic activity should therefore be limited after sampling to understand their biosynthesis in the berry and genetic regulation. In this study, berries were frozen in liquid nitrogen immediately after harvesting, transported in dry ice, stored briefly at −80 °C, cryo-milled and extracted without being thawed in cold methanol in a ratio of 1:4 (w/v). A UHPLC-MS/MS method for quantitative determination of the thiol precursors 3-S-glutathionylhexan-1-ol (G3MH), 3-S-cysteinylhexan-1-ol (Cys3MH), 4-S-glutathionyl-4-methylpentan-2-one (G4MMP) and 4-S-cysteinyl-4-methylpentan-2-one (Cys4MMP), glutathione, oxidized glutathione and L-methionine in grapes was developed. Reference material was provided through synthesis of precursors and their deuterium labelled analogues. The average thiol precursor content in grapes in 2013–15 was in the range 8–16 μg kg−1 for G3MH, 1–6 μg kg−1 for Cys3MH, 1–4 μg kg−1 for Cys4MMP and 0.3 μg kg−1 for G4MMP. In 2013 and 2014, the highest precursor content in mature Sauvignon Blanc grapes from vineyards located in Italy regarded G3MH, followed by Cys3MH, Cys4MMP and G4MMP. In 2015, G3MH was again the most abundant precursor, but followed by Cys4MMP, Cys3MH and G4MMP.